(untitled) (مجلة المنصور, 2025)
The current study attempts a multimodal discourse analysis of selected visual poems in the book “Five Oceans in a Teaspoon” written by Dennis Bernstein and visualized by Warren Lehrer. This book is seen as a reflection of everyday struggles and how to survive in the face of diversity. It is a memoir representing the struggles, love, pain, and loss in the writer’s life journey. The present study aims to help the audience interpret visual poems and the hidden cognitive background in these poems. Also, the study seeks to show how multimodal discourse analysis represents everyday problems and struggles visually and linguistically. The adopted analysis of the selected poems is a multimodal discourse analysis following Forcville's (2016) approach to interpreting the visualized poems and the interpretation of the cognitive background that represents hidden ideologies. To sum up, using multimodal metaphors helps reinforce the understanding of psychological and social stereotypes in society.